Moving from oral poliovirus vaccine to inactivated poliovirus vaccine: The rationale and challenges (Bangladesh Journal of Medicine, 2019)
Oral polio vaccine (OPV) has served as the cornerstone of polio eradication efforts over the past 30 years, trivalent inactivated polio vaccine (IPV) has re-ascended to prominence in the past year, now acting as the sole source of protective immunity against type 2 poliovirus in routine immunization programmes. The Polio Eradication and Endgame Strategic plan 2013–2018, developed by the Global Polio Eradication Initiative (GPEI) outlines the phased removal of OPVs, starting with type 2 poliovirus–containing vaccines and introduction of inactivated polio vaccine in routine immunization to mitigate against risk of vaccine-associated paralytic polio and circulating vaccine-derived poliovirus.Bangladesh J Medicine Jan 2020; 31(1) : 22-28